Harmonising RPJMD Regulation Dualism: Ta’arudh Al-Adillah Approach for Legal Certainty in Indonesia - Gunawan, Arief (Siyasah Dusturiyah: State Law Review, 2025)
This research analyses the dualism in the regulation of determining Regional Medium Term Development Plans (RPJMD) between Law Number 25 of 2004 concerning the National Development Planning System (UU SPPN) and Law Number 23 of 2014 concerning Regional Government (UU Pemda). Legal uncertainty arises due to differences in three crucial aspects: the type of legal product (Perkada or Perda), the time limit for enactment (3 months or 6 months), and the drafting mechanism. Using normative legal research methods with statutory and conceptual approaches, this study applies the Ta'arudh Al-Adillah perspective - the concept of postulate conflict resolution in ushul fiqh - to harmonise regulations. The research results identified three conflict resolution methods: al-jam'u wa al-taufiq (reconciliation), which views the two legal instruments as complementary, tarjih (preference), which prioritisesprioritizes the Regional Government Law as the lex specialis and lex posterior, and nasakh (abrogation), which ignores the formal-procedural aspects of the SPPN Law. This study concludes that the al-takhsis bi al-zaman (temporal specialisation) approach can be implemented gradually, where the Perkada functions as an emergency instrument for the first three months before being transformed into a Regional Regulation through DPRD discussions. Policy recommendations based on Fiqh Siyasah include the establishment of a national inter-institutional deliberative forum, development of a digital platform for synchronising the RPJMD-RPJMN, training on fiqh al-qanun al-idari for regional planners, and adoption of sharia performance indicators in RPJMD evaluation.